2009
DOI: 10.1111/j.1600-0609.2009.01310.x
|View full text |Cite
|
Sign up to set email alerts
|

Non‐transferrin‐bound iron in haematological patients during chemotherapy and conditioning for autologous stem cell transplantation

Abstract: Free iron induced hydroxyl radical formation is one possible mechanism for tissue injury during cytotoxic therapy. We studied the appearance of free, non-transferrin-bound iron (NTBI) at baseline and during the 20-d period after the onset of cytotoxic chemotherapy in patients with haematological malignancy undergoing intensive chemotherapy or conditioning for autologous stem cell transplantation (aSCT). NTBI was detected on average for 15.6 d in patients treated with chemotherapy only, and for 6.1 d in patient… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

4
21
0

Year Published

2010
2010
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 36 publications
(25 citation statements)
references
References 19 publications
4
21
0
Order By: Relevance
“…The pattern observed with LPI levels in our study matches patterns reported for NTBI levels in similar populations undergoing autologous HSCT [16,17]. The fact that the majority of the patients presented with increased LPI levels shortly after conditioning and during the aplasia phase and returned to having normal LPI levels upon engraftment is consistent with the hypothesis that inhibition and reconstitution of erythropoietic activity following myeloablative chemotherapy play a leading role in the kinetics of the appearance and disappearance of LPI [16].…”
Section: Discussionsupporting
confidence: 88%
See 2 more Smart Citations
“…The pattern observed with LPI levels in our study matches patterns reported for NTBI levels in similar populations undergoing autologous HSCT [16,17]. The fact that the majority of the patients presented with increased LPI levels shortly after conditioning and during the aplasia phase and returned to having normal LPI levels upon engraftment is consistent with the hypothesis that inhibition and reconstitution of erythropoietic activity following myeloablative chemotherapy play a leading role in the kinetics of the appearance and disappearance of LPI [16].…”
Section: Discussionsupporting
confidence: 88%
“…Some authors speculated on the impact of unbound iron in relation to toxicity in HSCT patients, based mainly on the fact that the time of appearance of NTBI concurred with the onset of toxicity [17,24]. In our study, it was shown that baseline LPI levels could predict the occurrence of grade III or IV toxicity.…”
Section: Discussionmentioning
confidence: 52%
See 1 more Smart Citation
“…On the basis of this, it would seem imprudent to use ferritin or MRI as surrogate markers for LPI, and large prospective studies measuring LPI will need to be done to determine whether this parameter influences HSCT outcomes. It may also be that the previously described increase in LPI after transplantation (in particular, from the conditioning regimen) [27] is more important than pre-HSCT LPI in mediating iron-dependent toxicity in this setting.…”
Section: Discussionmentioning
confidence: 99%
“…24 The inhibition of iron utilization in erythrocytes by chemotherapeutic agents and irradiation further increases NTBI levels. 25 Hydroxyl radical reactions by NTBI exacerbate mucosal damage caused by chemotherapeutic agents and irradiation, which allows bacterial organisms to enter through circulation. 26 In addition, iron is an important nutrient for the proliferation of bacteria and fungi.…”
Section: Discussionmentioning
confidence: 99%